2009
DOI: 10.1016/j.ijdevneu.2009.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Dietary selenium addition improves cerebrum and cerebellum impairments induced by methimazole in suckling rats

Abstract: The aim of this study is to investigate the improving effects of selenium (Se) on cerebrum and cerebellum impairments induced by methimazole (MMI) in suckling rats. Animals were randomly divided into four groups of six each: group I served as control which received standard diet; group II received only MMI (250 mg L(-1)(,) orally); group III received both MMI (250 mg L(-1), orally) and Se (0.5 mg kg(-1) of diet); group IV served as a positive control and received Se (0.5 mg kg(-1) of diet) as sodium selenite (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 74 publications
(83 reference statements)
3
25
0
Order By: Relevance
“…It has been shown that selenium plays an important role in the continuation of the physiological functions of the nervous system (such as signal transduction and development) (10). Previous studies have shown that selenium has a neuroprotective role in various experimental pathologies, such as spinal cord injury, cerebral ischemia and neurotoxicity models (11)(12)(13)(14)(15). Similarly, in our previous study, selenium prevented neurotoxicity that was induced by cisplatin in a partial level (16).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…It has been shown that selenium plays an important role in the continuation of the physiological functions of the nervous system (such as signal transduction and development) (10). Previous studies have shown that selenium has a neuroprotective role in various experimental pathologies, such as spinal cord injury, cerebral ischemia and neurotoxicity models (11)(12)(13)(14)(15). Similarly, in our previous study, selenium prevented neurotoxicity that was induced by cisplatin in a partial level (16).…”
Section: Introductionsupporting
confidence: 70%
“…Previous studies conducted with neurotoxic agents have demonstrated the neuroprotective effect of selenium on the central and peripheral nervous systems (8,(13)(14)(15)(16). However, this study was the first to demonstrate that selenium has a neuroprotective effect on peripheral nerve injury in rats.…”
Section: Discussionmentioning
confidence: 58%
“…The K 2 Cr 2 O 7 dose was selected on the basis of previous studies [43][44][45]. The Se dose (0.5 mg/kg of diet), used in our experiment and in other findings, gave high protection against stress conditions [10]. According to Hotz et al [37], lower doses of Se gave less protection, while higher doses were not much effective.…”
Section: Animalsmentioning
confidence: 90%
“…Selenoproteins contribute to thyroid hormone biosynthesis, antioxidant defense, redox control of thyrocytes, and thyroid hormone metabolism. The pathological consequences associated with hypothyroidism are attributed to antioxidant imbalances, which is why Se supplementation is also recommended for the treatment of hypothyroidism (Ben Amara et al, 2009). Thyroid hormones have important roles in embryogenesis and fetal maturation and regulate many key biochemical reactions, especially protein synthesis and enzymatic activity.…”
Section: Physiological Roles Of Selenoproteinsmentioning
confidence: 99%